2021
DOI: 10.1007/s00247-021-04992-2
|View full text |Cite
|
Sign up to set email alerts
|

Training physicians in India to interpret pediatric chest radiographs according to World Health Organization research methodology

Abstract: Background Chest radiography is the standard for diagnosing pediatric lower respiratory infections in low-income and middle-income countries. A method for interpreting pediatric chest radiographs for research endpoints was recently updated by the World Health Organization (WHO) Chest Radiography in Epidemiological Studies project. Research in India required training local physicians to interpret chest radiographs following the WHO method. Objective To desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…Despite modifications to the LDHF training approach and modest gains in knowledge from the training, it is important to note that we did observe improvement in examination scores among nearly all participants. Overall, this shows that appropriate education and training can improve knowledge gaps, and this is consistent with prior experience 13 14. The three physicians who participated in the training did score well on the post-training examination, achieving an average score of 90%.…”
Section: Discussionsupporting
confidence: 79%
“…Despite modifications to the LDHF training approach and modest gains in knowledge from the training, it is important to note that we did observe improvement in examination scores among nearly all participants. Overall, this shows that appropriate education and training can improve knowledge gaps, and this is consistent with prior experience 13 14. The three physicians who participated in the training did score well on the post-training examination, achieving an average score of 90%.…”
Section: Discussionsupporting
confidence: 79%
“…Overall, this shows that appropriate education and training can improve knowledge gaps, and this is consistent with prior experience. 13,14 The three physicians that participated in the training did score well on the post-training examination, achieving an average score of 90%. While our evaluation only examined short-term knowledge retention other studies have found similar educational programs may still promote both long-term retention as well as benefit clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%